William Laird McKinlay, 1889-1983 - White, Gavin (ARCTIC, 1983)
William Laird McKinlay, one of the scientific staff of the Canadian Arctic Expedition of 1913-18, died at G1asgow on 9 May 1983 at the age of 94. The son of a factory moulder in the industrial town of Clydebank downriver from Glasgow, he became a pupil-teacher at the age of 14 and subsequently studied at the University of Glasgow where he graduated both M.A. and B.Sc. in 1910. It was during his student days that his aid was enlisted by Dr. W.S. Bruce in classifying specimens brought home by the Scottish Antarctic Expedition, and this was to change his life. In 1913 he was teaching mathematics in a Glasgow school when Bruce recommended him to Viljhalmar Stefansson for appointment as meteorologist and magnetologist. McKinlay travelled to Esquimalt, B.C., where he joined the main party aboard Karluk, commanded by the veteran Newfoundlander Bob Bartlett, with Stefansson himself in overall charge. Discord made itself felt at an early stage. When Karluk was trapped in the ice off the north shore of Alaska, Stefansson and his companions went hunting ashore; weather separated them from the ship which drifted to the west while Stefansson occupied himself with the sledge travel, at which he was adept, and discovered new lands to the far north. Karluk turned out to be less than ideal for work in ice, while her crew had only been hired for a round trip and were largely unprepared for privations. After drifting with the ice for over six months, the ship was crushed and sank. Four men made their way to Herald Island where they died. Four others struck out on their own and were never seen again. The others, eleven crewmen and scientists with two Eskimo men, one Eskimo woman, and two Eskimo children, took what supplies they could to Wrangel Island 80 miles away. Then Bartlett and the Eskimo Kataktovik made an epic journey across the ice to the Siberian mainland in search of help. Those who remained on Wrangel Island divided into small groups and eked out a miserable existence in which two died, .; one seemingly shot himself. ...